Misbachul Watan Pelopor Pendidikan Islam Formal Berwawasan Kebangsaan di Malang 1923: Kajian Sejarah dan Perkembangan - Ayundasari, Lutfiah (Institut Agama Islam Negeri (IAIN) Tulungagung, 2019)
The aim of this study is to trace the history of Islamic education that has existed since the colonial period. It is important to give an understanding for the present and future generation about the struggle of predecessors to fight for independence and to maintain unity within the framework of national life. In addition, research on national insights is expected to be a filter of the emergence of organizations, ideologies, and information causing a rift of national relations. This research was conducted in Malang, precisely in district Singosari that well known Kota Santri. The background as a center of the education of Islamic boarding school apparently does not restrict Kiai’s thought to formulate an modern education model. The data is collected with interactive techniques such as interviews and non-interactive techniques namely studies of documents or related archives. The results of this research include the historical description of Misbachul Watan, the foundation of the founding ideology of the school that is deduced from the biography of the founder, and the development and sustainability of Misbachul Watan with a new name that still shows His role in caring for an nationalism in an Islamic educational institution